(untitled) (Journal of the Bangladesh Chemical Society, 2012)
Kinetics of the alkaline hydrolysis of crystal violet (CV) in micelles, reverse micelles and microemulsions of a cationic surfactant, cetyltrimethylammonium bromide (CTAB) was studied at 25 ± 0.1 oC using spectrophotometric method. The rate of alkaline hydrolysis of CV was catalyzed by micellar solutions of CTAB. The pseudo first order rate constant (k’) has been found to decrease upon incorporation of 1-butanol to cationic CTAB micelles, which displaces the substrate from the micellar into the aqueous phase. In CTAB/cyclohexane/1-butanol/water system, as the content of 1-butanol increases, specific conductivity and density of the microemulsions and reverse micelles decrease. The change in physical properties also causes change in reaction environment. A change from a micelle-rich (o/w) to a reverse micelle-rich (w/o) condition is apparent for microemulsions and consequently the k’ vs. % wt. of 1-butanol profiles show an initial decrease in the k’ followed by a gradual increase and finally, to a sharp increase with increasing 1-butanol content. Microemulsions and reverse micelles thus offer the potential to control rate of a reaction by formation of micelles in water phase and reverse micelles in oil phase. DOI: http://dx.doi.org/10.3329/jbcs.v24i2.9706 Journal of Bangladesh Chemical Society, Vol. 24(2), 173-184, 2011